2007
DOI: 10.1182/blood-2007-03-077339
|View full text |Cite
|
Sign up to set email alerts
|

Screening for leukemia- and clone-specific markers at birth in children with T-cell precursor ALL suggests a predominantly postnatal origin

Abstract: Childhood T-cell precursor acute lymphoblastic leukemia (TCP ALL) is an aggressive disease with a presumably short latency that differs in many biologic respects from B-cell precursor (BCP) ALL. We therefore addressed the issue of in utero origin of this particular type of leukemia by tracing oncogenic mutations and clone-specific molecular markers back to birth. These markers included various first-and second-hit genetic alterations (TCRD-LMO2 breakpoint regions, n ‫؍‬ 2; TAL1 deletions, n ‫؍‬ 3; Notch1 mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 25 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…8 In line with various other leukemia clone-specific markers, we also confirmed that at least in cases with a major P2RY8-CRLF2-positive clone the fusion is already present at birth. [16][17][18][24][25][26][27] Apart from that, however, P2RY8-CRLF2-positive clones do not seem to have any particular proliferative or selective advantage and therefore also not the necessary fitness to evolve into a disease-relevant relapse clone. This view is supported by experiments showing in various model systems that neither fusion nor CRLF2 overexpression alone is sufficient to transform cells without the concomitant expression of certain activating mutations, such as those affecting the JAK2, CRLF2, or IL7R genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In line with various other leukemia clone-specific markers, we also confirmed that at least in cases with a major P2RY8-CRLF2-positive clone the fusion is already present at birth. [16][17][18][24][25][26][27] Apart from that, however, P2RY8-CRLF2-positive clones do not seem to have any particular proliferative or selective advantage and therefore also not the necessary fitness to evolve into a disease-relevant relapse clone. This view is supported by experiments showing in various model systems that neither fusion nor CRLF2 overexpression alone is sufficient to transform cells without the concomitant expression of certain activating mutations, such as those affecting the JAK2, CRLF2, or IL7R genes.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from one-third of a neonatal blood spot (Guthrie card), essentially as described previously with minor variations (see supplemental Figure 5). [16][17][18] From cases with the previously published breakpoints, the genomic fusion was determined in whole genome-amplified Guthrie card DNA by TaqMan qRT-PCR as described in "Quantification of genomic P2RY8-CRLF2." For the case with the newly identified breakpoint, a patientspecific nested 2-round PCR was established using a standard curve (10-log dilutions) from the respective diagnostic leukemia DNA.…”
Section: Patient Samplesmentioning
confidence: 99%
“…The development of pediatric ALL is a multistep process driven by the accumulation of two types of genetic abnormalities, (i) 1 st hit, often a chromosomal translocation generating a pre-leukemic fusion gene (PFG), and (ii) 2 nd hit, often point mutations, deletions, duplications. Several data, including studies in identical twins and with neonatal spots (Guthrie cards) have suggested that the initiation of childhood ALL-associated chromosomal translocations may arise in utero during fetal hematopoiesis [3–9]. The resultant fusion gene product with a novel activity, different from the activities of individual partner genes, produces a persistent, but covert pre-leukemic clone [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Less is known of the preleukemic (subclinical) phase for other subsets of childhood ALL, but Guthrie card and twin/triplet studies indicate that t(1;19)(q23;p13)[E2A-PBX1] translocation-positive cases and T-lineage ALL in general are initiated postnatally. [19][20][21] GCs are among the most important and effective inducers of apoptosis in normal and malignant lymphoblasts both in vitro and in vivo. 22,23 As monotherapy, both prednisolone and prednisone, which after absorption rapidly is converted to prednisolone, can induce morphological remission.…”
mentioning
confidence: 99%